Leonardo Bruni’s Hendecasyllabi between imitatio and aemulatio of Catullian style (Minerva, 2023)
Catullus was the Latin poet who aroused the most interest in the humanistic period in the Renaissance, especially for his non-conformism that challenged social and literary conventions. His language, often outrageous on the one hand, and poignant and intimist on the other, fascinated generations of Renaissance poets who sought to bring the Latin language back along with their mother tongue in order to respond to the increasingly and overwhelming growth of vernacular literature and create a community of Latin poets capable of communicating with each other across Europe. Leonardo Bruni had the merit of being the first among the humanists to experiment with that obscene lexicon and a style characterised by an exaggeration of phonic and rhetorical effects aimed at emphasising the theme expressed. His poetry is influenced by the Catullan taste for direct attack, the best expression of which is the hendecasyllable itself; iuncturae and stylistic devices or paraphrases of the same verses taken from poems such as 41, 42 and 29 flow into Bruni’s text. The rendering of repetitions, phonic effects, hyperbolic images and the libellous lexicon itself reach emulative levels that go beyond the pure imitatio of Catullus.
Keywords: Catullus; Renaissance; Humanism in the Renaissance; Leonardo Bruni; imitatio; aemulatio; Hendecasyllabi